Pluchea indica: An updated review of its botany, uses, bioactive compounds and pharmacological properties - Eric Wei Chiang Chan; Ying Ki Ng; Siu Kuin Wong; Hung Tuck Chan (Faculty of Pharmacy, Mahidol University, 2022)
In this article, the botany, uses, bioactive compounds and pharmacological properties of leaves and roots of Pluchea indica are reviewed for the first time. The coastal species occurs in open sites at the landward side of mangroves. Main botanical characters for the identification of P. indica are bushy shrub life-form, and leaves are short-stalked, obovate, thick papery, tapering base and serrated margin. Crushed leaves are very aromatic. Its traditional uses take the form of medicine and food. The pharmacological properties of P. indica are focused on its antioxidant, antibacterial, anti-cancer and anti-inflammatory activities. Caffeoylquinic acids and terpene glycosides are the main bioactive compounds from aerial parts and leaves of P. indica, respectively. Antioxidant properties of P. indica leaves have been reported to be stronger than those of Curcuma longa turmeric rhizomes. Also reported is that P. indica tea has stronger antioxidant properties of than green tea of Camellia sinensis. Leaves and roots of P. indica including tea leaves inhibit the growth of Gram-positive and Gram-negative bacteria, and possess anti-inflammatory properties. Roots are cytotoxic to cancer cells. Leaves and roots of P. indica also possess a range of other bioactivities. Some future research and prospects are suggested.